Language ideologies against norm change: A case study of the orthographic norm of Finnish O(i)ttA-verbs and language professionals’ unwillingness to change it - Pajunen Henni (University of Tartu Press, 2025)
This study investigates why language professionals of the standard Finnish language are unwilling to change a known problematic orthographic norm and how their arguments are based on overt and covert conceptions of standard language. It also analyzes how dominant language ideologies, namely standard language ideology (SLI) and linguistic purism, form the bases of these conceptions. The study is based on a qualitative survey, and it explores the metalanguage of the answers to one open-ended question using content analysis.
The concepts of language are presented as conceptual metaphors. The analysis reveals six concepts that represent a particular ideological notion belonging to purism, SLI, or both. The respondents conceptualize language as value judgments and through functions and social connotations. Some concepts are based on non-linguistic but emotionally powerful values, others on usability or language’s ability to serve as a marker of status or social bonds. The study highlights the deep impact of language ideologies.